HOUT-04. ASSOCIATION OF COMMON PATIENT-REPORTED IMMUNOTHERAPY SYMPTOMATIC SIDE EFFECTS AND PSEUDOPROGRESSION IN PATIENTS WITH PRIMARY CENTRAL NERVOUS SYSTEM (CNS) TUMORS. (11th November 2019) - Vyas, Yamini; Vera, Elizabeth; Bryla, Christine; Crandon, Sonja; Wu, Jing; Wall, Kathleen; Theeler, Brett; Siegel, Christine; Reyes, Jennifer; Penas-Prado, Marta; Leggiero, Nicole; Cordova, Christine; et al.
Abstract: BACKGROUND: Immunotherapy agents have unique symptomatic side effects; patient-reported outcomes (PROs) can help to characterize the benefits and burdens associated with therapy. Common immunotherapy-associated symptoms include pain, fatigue, shortness of breath, and irregular bowel patterns. The purpose of this study was to assess the severity of symptoms and their association with imaging changes in CNS tumor patients undergoing single agent or combination treatment with immune checkpoint inhibitors (ICIs). METHODS: Patients completed the MDASI-BT or MDASI-SP at baseline and longitudinally (every 8 weeks), and results through cycle 4 are reported. Neuro-imaging was categorized as stable, possible ICI-related pseudoprogression, or progression by clinical team review. RESULTS: 29 Brain Tumor (BT) and 6 Spinal Tumor patients participated; the majority of which were male (62%) and white (91%), ranging 24-74yo (mean = 46). Glioblastoma was the most common diagnosis (31%) followed by medulloblastoma (16%), with 56% of patients having greater than 2 recurrences prior to the study. At baseline, both brain and spine tumor patients reported moderate to severe fatigue (Brain=4, Spine=6) and pain (Spine=5) with shortness of breath and pain worsening over time. BT patients with pseudoprogression were more likely to report increased fatigue (87%) and pain (63%) compared to those with stable (29%) or true progressive (17%) disease on imaging. BT patients with pseudoprogression also reported worsening of cognitive (43%) and neurologic (57%) symptom burden. CONCLUSIONS: In contrast to the common pseudoprogression after chemoradiation, treatment-specific symptoms were worse with ICI-related pseudoprogression by MRI where an immunologic reaction was the likely cause of the imaging worsening. These results suggest that commonly used symptom and functional assessments to distinguish true progression from pseudoprogression may not be helpful with immunotherapy. Additional studies including those with pathologic confirmation of progression or pseudoprogression combined with outcomes measures are needed to develop more accurate determinations of disease status.